1989
DOI: 10.1177/036354658901700106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic EMG analysis of anterior cruciate deficient legs with and without bracing during cutting

Abstract: The purpose of this research was to determine if bracing altered muscle firing amplitude, duration, or timing, creating improved dynamic stability. We hypothesized that a derotational knee brace improved the stability of an ACL deficient knee by augmenting limb proprioception, causing hamstring muscles to increase in activity and/or to contract earlier during a side-step cut. Ten subjects with documented unilateral isolated ACL deficient knees and five normal controls participated. A strap dominant brace (Leno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
3

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 21 publications
2
62
1
3
Order By: Relevance
“…Previous manual knee evaluations including the anterior drawer test, the pivot shij? test, and Lnchman 's test have al1 rneasured tibial displacements during simulated static loading conditions but they do not reflect true physiologic loading (Branch et al, 1989).…”
Section: Hypo Thesismentioning
confidence: 99%
See 4 more Smart Citations
“…Previous manual knee evaluations including the anterior drawer test, the pivot shij? test, and Lnchman 's test have al1 rneasured tibial displacements during simulated static loading conditions but they do not reflect true physiologic loading (Branch et al, 1989).…”
Section: Hypo Thesismentioning
confidence: 99%
“…Early studies reported fewer syrnptoms of instability with improved athletic performance during brace use although evaluations were anecdotal and subjective in nature (Vailas et ai., 1990 However, braces seem to fail in situations where high loads are encountered or when the load is applied in an unpredictable manner (Branch et al, 1989).…”
Section: Functional Bracingmentioning
confidence: 99%
See 3 more Smart Citations